SISTEM PENGENDALIAN MANAJEMEN PADA BADAN USAHA MILIK DESA LUMBUNG SEWU DALAM MENINGKATKAN PENDAPATAN ASLI DESA SEWUREJO - Suryowati, Alam Suprobo; Daljono, Daljono (Diponegoro Journal of Accounting, 2024)
Efforts to increase Village Original Income (VOI) through Village-Owned Enterprises (VOE) require an appropriate Management Control System (MCS) to ensure that the activities carried out are in accordance with the goals the organization wants to achieve.This research aims to determine the application of MCS in VOE Lumbung Sewu in improving VOI Sewurejo. This research is descriptive research, with data collection methods through observation, interviews and documentation. The data analysis technique was carried out using the Charmaz Coding method, where coding of interview results was carried out to assist in grouping specific interview results which showed a relationship with other data. There are two steps in coding, namely coding done line by line and coding done word by word, followed by focused coding.The research results show that the management control system at BUMDes Lumbung Sewu is not running optimally. This is caused by several factors, including in terms of organization, business unit management, community support, and capital. BUMDes Lumbung Sewu can take steps to optimize its business by improving the quality of human resources, good capital management, developing business units, involving the participatory role of the community.